Aktivitas Antioksidan Dan Uji Organoleptik Minuman HerbalEkstrak Tanaman Krokot (Portulaca oleracea L.) Dengan Variasi Penambahan Daun Stevia Dan Kelopak Bunga Rosella - Fitriani, Eka Wahyu; , Dra. Suparti M,Si (2016)
Herbal drink is one of the natural plant -based drink that is beneficial for the body . Basic herbal drink made with herbs , roots , stems , leaves, roots and fruits. Currently herbal drink made by extracting natural plant materials with modern technology . One innovation is the herbal beverage ingredients purslane plants . Plants Purslane is one weed that is known to have many benefits, but can not be used scientifically. Purslane has a concentration of omega-3 fatty acids high and two kinds of pigment betalain betaxantin alkaloid and a powerful antioxidant. Stevia leaves is one of the plants that contain glycosides that have the opportunity as a natural sweetener alternative low-calorie sugar substitute. There rosella flower petals that form the flavonoid anthocyanin pigments that act as antioxidants. This study aims to determine antioxidant activity and organoleptic qualities of purslane herb extract drink with the addition of stevia leaf variation and rosella flower petals. The study design used completely randomized design two factors: a factor of 1: formulation rosella flower petals (1g, 2.5g, 5g) and 2 factors: dose of stevia leaves (0,6g, 0,9g) with three replications. Analysis of the data used in this study is one way anova test for antioxidant activity and qualitative descriptive analysis for organoleptic drink purslane herb extract. According to the research the highest antioxidant activity drink purslane herb extract in treatment R3S2 (50ml purslane extract formulations with variations rosella flower petals 5g and stevia leaves 0,9g) that is equal to 77.09 %. Best quality herbal drink to the organoleptic properties of color , flavor , and the acceptance that the treatment R3S2 with purslane extract 50ml , stevia leaves 0,9g and rosella flower petals 5g which has a red color, a distinctive aroma of purslane , taste less sweet and more acceptance preferred by the panelists.